Sinergi antara Lembaga Pemerintah melalui E-Government: Kajian Implementasi dan Tantangan Kolaboratif - Vivi Venti Vera Sulila; Sri Yulianty Mozin (Lembaga Pengembangan Kinerja Dosen, 2025)
This article analyzes inter-agency synergy in Indonesia through e-Government as a foundation for collaborative governance. The study investigates how digital governance creates coordination, interoperable data exchange, and transparency among ministries and government agencies, and maps the collaborative challenges that impede implementation. Using a qualitative descriptive approach based on policy analysis and literature review, the paper synthesizes Indonesia’s SPBE (Electronic-Based Government System) policy regime, national initiatives such as Satu Data Indonesia and GovTech (INA Digital), and recent scholarly findings on collaborative and agile governance. Findings indicate that e-Government enhances synergy through integrated platforms, shared standards, and institutionalized coordination, yet progress is uneven due to bureaucratic silos, fragmented legacy systems, regulatory ambiguity at the technical level, cyber-security risks, and human-capital gaps. The paper argues that sustained leadership, a national interoperability framework, trust-based data governance, and capability development are decisive enablers. The implications highlight the need to institutionalize cross-agency stewardship, align performance metrics with collaboration outcomes, and embed agile routines to adapt to fast-changing technologies.